Kontroversi Rating di Belantara Industri Televisi - Iwan Awaluddin Yusuf; Pratiwi Utami (Program Studi Ilmu Komunikasi, 2007)
Rating indeed determines selling price of the program to the advertiser. The higher rating brings the greater number of advertiser. The greater advertiser then means a better life of a TV station. As a consequence, almost all TV station is competing to produce a program that could “buy” market and advertiser, even though they must decrease the quality of TV program's contents. In the other hand, rating itself is a controversy. The rating system gets sharp critics due to its weakness, both from methodological and technical sides. Basically, rating couldn't represent a deeper viewing behavior of the audience, the audience's focus when watching TV, et cetera. This article will elaborate how rating works in Indonesian TV industry. The relation between rating, advertisement, advertiser, and the market share will be explained. The discussion in this writing will develop on the subject of the debates and controversy around rating.